PENGARUH PEMBERIAN KOMPRES KOL TERHADAP PENURUNAN PEMBENGKAKAN PAYUDARA PADA IBU POST PARTUM DI KLINIK BERSALIN KASIH IBU DELI TUA KABUPATEN DELI SERDANG TAHUN 2019 - Putri Ayu Yessy Ariescha; Andayani Boang Manalu; Nurul Aini Siagian; Mutiara Dwi Yanti; Rehulina Tarigan (Fakultas Kebidanan Institut Kesehatan Medistra Lubuk Pakam, 2020)
One of common problems associated with breastfeeding is breast engorgement. This breast swelling can cause the mother to stop breastfeeding. This study aims to determine the effect of cabbage compresses on reducing breast engorgement in postpartum mothers at Kasih Ibu Primary Clinic in Deli Tua in 2019. The research used quasi-experimental, one-group pretest-posttest method design. The sampling technique used convenience sampling to recruit 30 postpartum mothers who had breast engorgement. The instrument used to measure breast swelling was the breast engorgement assessment scale of Hill and Hummenick which consisting of a scale of 1 to 6. Application of cabbage compresses was done by attaching cabbage to the breast until the cabbage withers. This procedure was repeated four times every 6 hours per day, for 2 days. The results of the study showed that at the time before being compressed all the research subjects had a score of 4. On the 1st day of compressing with cabbage leaves, there were 7 people (23.3%) who had decreased breast swelling and on the 2nd day of compressing, the total postpartum mothers experienced a decreased in breast engorgement was 9 people (30%). Statistical analysis by paired t-test obtained the value of p = 0.001 (p <0.05). Thus, the results of this study concluded that there was a significant influence of cabbage compresses to decrease breast engorgement of the postpartum mothers at Kasih Ibu Primary Clinic in Deli Tua in 2019.